Brain structure analysis of different age groups of Diannan small‐ear pigs. Issue 3 (13th August 2022) - Liu, Yi‐Fan; Fang, Chang‐Le; Pi, Yu; Ke, Teng‐Fei; Chu, Ji‐Xiang; Tang, Lin‐Na; Zhang, Lan‐Chun; Wanchana, Somjit; Liao, Cheng‐De
Abstract: The objective of the study is to investigate the brain development and atrophy of Diannan small‐ear pigs in different ages using magnetic resonance imaging (MRI). A total of 12 Diannan small‐ear pigs were included and divided into the young group, adult group, and middle‐and‐old age (M&O) group according to their age. The brain structure of pigs was scanned using MRI, and the brain data obtained were statistically analyzed by signal conversion and image reconstruction. Compared with the young group, the signals of most brain structures in the adult group and M&O group were significantly decreased ( p < 0.05). Compared with the adult group, the signal intensity of the right caudate nucleus and the right lateral ventricle in the M&O group was significantly increased, while the signal intensity of other regions was almost significantly decreased ( p < 0.05). Compared with the young group, both adult and M&O groups had some degree of brain atrophy. Brain atrophy in the precuneus and the inferior temporal gyrus was more predominant in the M&O group in comparison with the adult group. The present study demonstrated that the brain signal of Diannan small‐ear pigs gradually diminished with age, while the degree of brain atrophy was the opposite, providing the basic data on the brain of Diannan small‐ear pigs. Abstract : In this study, structural brain images of three groups of Diannnan small‐ear pigs of different ages were scanned by magnetic resonance imaging, 3D images were constructed for whole‐brain images and VBM analysis of T2 structural images was performed, and the results were compared cross‐sectionally and longitudinally. The results revealed that brain development and brain atrophy were closely related to age. In this study, the basic brain tissue data were measured in Diannnan small‐ear pigs to provide basic data for the development of brain test standards, related studies, and modeling of related brain diseases in Diannnan small‐ear pigs.